2002
DOI: 10.1034/j.1600-079x.2002.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by melatonin against ischemic neuronal injury associated with modulation of DNA damage and repair in the rat following a transient cerebral ischemia

Abstract: In the present study, double fluorescence staining combined with confocal laser scanning microscopy analysis were used to examine the effects of melatonin on ischemia-induced neuronal DNA strand breaks and its possible mechanisms in a transient middle cerebral artery (MCA) occlusion model. Results showed that melatonin dose-dependently reduced infarct areas and decreased both DNA double and single strand breaks (DSB and SSB) and enhanced cell viability in the peri-ischemic brain regions. Furthermore, Bcl-2 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 39 publications
6
86
0
3
Order By: Relevance
“…Melatonin has been shown to upregulate excision repair cross-complementing group 6 (ERCC6) mRNA expression in the peri-ischemic region of rat brains. 13 Vascular endothelial growth factor antisense treatment resulted in increased infarct volume and decreased ischemia-induced ERCC6 expression in the rat brain. 14,15 Moreover, IP markedly increased BER activity, whereas simultaneously reducing the nuclear accumulation of several oxidative DNA lesions following subsequent severe ischemia.…”
Section: Introductionmentioning
confidence: 97%
“…Melatonin has been shown to upregulate excision repair cross-complementing group 6 (ERCC6) mRNA expression in the peri-ischemic region of rat brains. 13 Vascular endothelial growth factor antisense treatment resulted in increased infarct volume and decreased ischemia-induced ERCC6 expression in the rat brain. 14,15 Moreover, IP markedly increased BER activity, whereas simultaneously reducing the nuclear accumulation of several oxidative DNA lesions following subsequent severe ischemia.…”
Section: Introductionmentioning
confidence: 97%
“…The pineal hormone melatonin is synthesized in the pinealocytes of the pineal gland with an endogenous rhythm and has a role in many physiological and pathological processes in human. At present, there are a number of conditions, which are said to be improved by administration of melatonin (Joo et al, 1998;Cuzzocrea et al, 2000;Sun et al, 2002;Pei et al, 2003). Recently, Pei et al, (2003) suggested that treatment with melatonin significantly reduced both the infarct volume and the brain nitric oxide production due to cerebral ischemia in rat stroke models (Anwar et al, 2001) reported that melatonin has an endothelium dependent vasorelaxant effect due to lowered calcium content in vascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, melatonin supplementation suppresses NO-induced apoptosis via induction of Bcl-2 expression in immortalized pineal PGT-cells (Yim et al 2002). A similar pathway of inhibitory effects of melatonin on apoptosis induced by ischemic neuronal injury has been determined (Sun et al 2002).…”
Section: Melatonin Modulates Apoptosis In Radiotherapy and Space Radimentioning
confidence: 98%